2018
DOI: 10.1096/fj.201700247rr
|View full text |Cite
|
Sign up to set email alerts
|

Near‐tetraploid cancer cells show chromosome instability triggered by replication stress and exhibit enhanced invasiveness

Abstract: A considerable proportion of tumors exhibit aneuploid karyotypes, likely resulting from the progressive loss of chromosomes after whole-genome duplication. Here, by using isogenic diploid and near-tetraploid (4N) single-cell-derived clones from the same parental cell lines, we aimed at exploring how polyploidization affects cellular functions and how tetraploidy generates chromosome instability. Gene expression profiling in 4N clones revealed a significant enrichment of transcripts involved in cell cycle and D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 61 publications
5
60
0
Order By: Relevance
“…4d-e). These data reveal that WGD + tumor cells are more dependent on specific DNA replication factors relative to WGD − tumor cells, perhaps as a means to compensate for increased replication stress induced by tetraploidy 41,42 . These results are particularly significant in therapeutic contexts as gemcitabine and other inhibitors of ribonucleotide reductase represent the standard of care for treatment regimens across multiple cancer subtypes, and biomarkers that can predict sensitivity to gemcitabine hold real prognostic value 43 .…”
Section: Wgd Confers Unique Genetic Vulnerabilities On Tumorsmentioning
confidence: 83%
“…4d-e). These data reveal that WGD + tumor cells are more dependent on specific DNA replication factors relative to WGD − tumor cells, perhaps as a means to compensate for increased replication stress induced by tetraploidy 41,42 . These results are particularly significant in therapeutic contexts as gemcitabine and other inhibitors of ribonucleotide reductase represent the standard of care for treatment regimens across multiple cancer subtypes, and biomarkers that can predict sensitivity to gemcitabine hold real prognostic value 43 .…”
Section: Wgd Confers Unique Genetic Vulnerabilities On Tumorsmentioning
confidence: 83%
“…It has been posited that polyploid tumors with elevated genomic content tend to become resistant to chemotherapy due to rapid tumor evolution (49). In addition, neartetraploid cancer cells have recently been shown to exhibit enhanced invasiveness (50). It will be of interest to determine whether high ploidy status per se is able to contribute to SASPinduced tumor progression.…”
Section: Wwwaacrjournalsorgmentioning
confidence: 99%
“…23), supporting the potential role of polyploidy in tumour development. A recent study reported that near-tetraploid cancer cells exhibited elevated invasiveness and displayed CIN (215), lending support to our findings. Our results therefore describe another mechanism by which polyploidization per se has the potential to contribute to tumourigenesis through senescence and SASP.…”
Section: Potential Role Of Polyploidy In Senescence and Tumourigenesissupporting
confidence: 91%
“…Notably, we observed an enrichment of cells displaying 3 or more signals for these two chromosomes at the invasive fronts compared to cells in the centre region and the normal area, suggesting the existence of near-triploid and near-tetraploid cells at the invasive front. This finding is in line with a recent study that revealed the presence of near-tetraploid cancer cells at the invasive front in primary colorectal tumours, which led to their speculation that tetraploidy could promote the invasiveness and aggressiveness of cancer cells (215). Importantly, our study revealed a correlation of greater deviation from the diploidy with increased incidence of senescence and SASP at the invasion front, indicating that the pro-tumourgenic paracrine effects of SASP from senescent tumour cells might plausibly promote the aggressive behaviour of tumour cells at the invasive front, as described previously in vitro.…”
Section: Senescent and Aneuploid Cells Are Frequently Present At The supporting
confidence: 90%